Mitochondria regulate intracellular coenzyme Q transport and ferroptotic resistance via STARD7 - Deshwal, Soni; Onishi, Mashun; Tatsuta, Takashi; Bartsch, Tim; Cors, Eileen; Ried, Katharina; Lemke, Kathrin; Nolte, Hendrik; Giavalisco, Patrick; Langer, Thomas (Nature cell biology, 2023)
Coenzyme Q (or ubiquinone) is a redox-active lipid that serves as universal electron carrier in the mitochondrial respiratory chain and antioxidant in the plasma membrane limiting lipid peroxidation and ferroptosis. Mechanisms allowing cellular coenzyme Q distribution after synthesis within mitochondria are not understood. Here we identify the cytosolic lipid transfer protein STARD7 as a critical factor of intracellular coenzyme Q transport and suppressor of ferroptosis. Dual localization of STARD7 to the intermembrane space of mitochondria and the cytosol upon cleavage by the rhomboid protease PARL ensures the synthesis of coenzyme Q in mitochondria and its transport to the plasma membrane. While mitochondrial STARD7 preserves coenzyme Q synthesis, oxidative phosphorylation function and cristae morphogenesis, cytosolic STARD7 is required for the transport of coenzyme Q to the plasma membrane and protects against ferroptosis. A coenzyme Q variant competes with phosphatidylcholine for binding to purified STARD7 in vitro. Overexpression of cytosolic STARD7 increases ferroptotic resistance of the cells, but limits coenzyme Q abundance in mitochondria and respiratory cell growth. Our findings thus demonstrate the need to coordinate coenzyme Q synthesis and cellular distribution by PARL-mediated STARD7 processing and identify PARL and STARD7 as promising targets to interfere with ferroptosis. Deshwal et al. show that the protease PARL regulates coenzyme Q (CoQ) via the lipid transfer protein STARD7. Mitochondrial STARD7 ensures CoQ synthesis; cytosolic STARD7 preserves CoQ transport to the membrane, protecting cells against ferroptosis.